Neuraxial anaesthesia and peripheral nerve blocks during the COVID‐19 pandemic: a literature review and practice recommendations. (14th May 2020) - Uppal, V.; Sondekoppam, R. V.; Landau, R.; El‐Boghdadly, K.; Narouze, S.; Kalagara, H. K. P.
Summary: Coronavirus disease 2019 (COVID‐19) has had a significant impact on global healthcare services. In an attempt to limit the spread of infection and to preserve healthcare resources, one commonly used strategy has been to postpone elective surgery, whilst maintaining the provision of anaesthetic care for urgent and emergency surgery. General anaesthesia with airway intervention leads to aerosol generation, which increases the risk of COVID‐19 contamination in operating rooms and significantly exposes the healthcare teams to COVID‐19 infection during both tracheal intubation and extubation. Therefore, the provision of regional anaesthesia may be key during this pandemic, as it may reduce the need for general anaesthesia and the associated risk from aerosol‐generating procedures. However, guidelines on the safe performance of regional anaesthesia in light of the COVID‐19 pandemic are limited. The goal of this review is to provide up‐to‐date, evidence‐based recommendations or expert opinion when evidence is limited, for performing regional anaesthesia procedures in patients with suspected or confirmed COVID‐19 infection. These recommendations focus on seven specific domains including: planning of resources and staffing; modifying the clinical environment; preparing equipment, supplies and drugs; selecting appropriate personal protective equipment; providing adequate oxygen therapy; assessing for and safely performing regional anaesthesia procedures; and monitoring during the conduct of anaesthesia and post‐anaesthetic care. Implicit in these recommendations is preserving patient safety whilst protecting healthcare providers from possible exposure.